Establishment of a French surveillance system of Clostridiodes difficile infection: Comparison of patient's characteristics with other national and European data. (June 2021) - Khanafer, Nagham; Hemmendinger, Anaelle; Guery, Benoit; Vachée, Anne; Rogues, Anne-Marie; Gravet, Alain; Boutoille, David; Vanjak, Dominique; Barbut, Frédéric; Vanhems, Philippe
Abstract: Introduction: The magnitude and scope of Clostridioides difficile infection (CDI) has changed with an increase in incidence and severity. The epidemiology of CDI is not well known in France due to difficulties to conduct large continuous surveillance. The objectives were to compare the characteristics of patients with CDI collected through repeated point prevalence survey via DIFTEC™, a free electronic tool, with those from previous French or European studies. Methods: DIFTEC™ was developed to evaluate epidemiological burden, diagnostic strategies and management of CDI in France. National and European guidelines were used for definitions. A literature review of studies conducted in Western Europe on CDI and published between January 2008 and May 2018 was done to compare their data with those included in the DIFTEC™ database. Results: From January 2016, to December 2017, 455 CDI episodes from 22 French hospitals were included. Most of CDI cases were health-care associated (HCA) (78%). The comparison between included patients and French literature data showed that the rates of previous antibiotics exposure, crude mortality and recurrence were not statistically different. However HCA-CDI was significantly more frequent in the DIFTEC™ study. Gender distribution, recurrence and crude mortality rates were not statistically different compared to European data. HCA-CDI was more frequent in the DIFTEC™ study whereas previous treatment with proton pump inhibitors and antibiotics were significantly higher in European studies. Discussion: These results illustrated the added value of a new tool for increasing the reliable knowledge of CDI in France based on epidemiological surveillance implemented in health-care settings. Graphical abstract: Image 1 Highlights: Difficulties to maintain prospective surveillance. Added value of a free electronic tool for increasing the reliable knowledge of CDI. An easy tool to include the surveillance of CDI into a daily monitoring. A generation of data to be shared at national and international level.